1999
DOI: 10.2307/2656756
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and structure of the narrow endemic Wyethia reticulata and its congener W. bolanderi (Asteraceae) using RAPD and allozyme techniques

Abstract: Wyethia reticulata is an edaphic endemic in the Sierra Nevada foothills. Its sympatric congener, W. bolanderi, is also restricted to the foothills, but has a north-south range of 275 km, compared to 14 km for W. reticulata. The goals of this study were to determine clonal diversity, population size, genetic variation, and spatial and generic structure for each species from paired populations in El Dorado County, California, using allozyme and RAPD (random amplified polymorphic DNA) methodologies. Wyethia retic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0
8

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 40 publications
5
55
0
8
Order By: Relevance
“…This result was consistent with previous studies in some invasive species (Chapman et al 2000;Ellstrand and Schierenbeck 2000;Meekins et al 2001;Mengistu and Messersmith 2002). Sexual reproduction can increase genetic variation (Ayres and Ryan 1999;Naito et al 1999) and allow natural selection to proceed more effectively (Burt 2000). So, in this study, sexual reproduction may be the primary reason for high genetic diversity.…”
Section: Discussionsupporting
confidence: 93%
“…This result was consistent with previous studies in some invasive species (Chapman et al 2000;Ellstrand and Schierenbeck 2000;Meekins et al 2001;Mengistu and Messersmith 2002). Sexual reproduction can increase genetic variation (Ayres and Ryan 1999;Naito et al 1999) and allow natural selection to proceed more effectively (Burt 2000). So, in this study, sexual reproduction may be the primary reason for high genetic diversity.…”
Section: Discussionsupporting
confidence: 93%
“…Genetic diversity F st or equivalent Population structure (cluster, …) Aagard et al, 1998 Allozymes Ͻ RAPDs Allozymes Х RAPDs Apostol et al, 1996 Allozymes Ͻ RAPDs Ayres and Ryan 1999 Allozymes Ն RAPDs a Regional scale concordance Bartish et al, 2000 Allozymes Ͻ RAPDs Allozymes Ͼ RAPDs Allozymes Х RAPDs Baruffi et al, 1994 Allozymes Wolf et al, 1998 Allozymes Ͻ RAPDs General congruence Haig et al, 1994 Allozymes Х RAPDs Allozymes RAPDs but neither resulted in overall assortment of clusters geographically Isabel et al, 1995 b Allozymes Х RAPDs Allozymes Х RAPDs Jenczewski et al, 1999 Allozymes Ͼ RAPDs Similar Agreement between the global patterns of populations structure Le Corre et al, 1997 Allozymes Ͼ RAPDs Allozymes Х RAPDs Allozymes RAPDs Liu and Furnier 1993 Allozymes Յ RAPDs* Mamuris et al, 1999 Allozymes Ͻ RAPDs Allozymes Ͻ RAPDs Isolation by distance observed in RAPDs, not in allozymes Oiki et al, 2001 Allozymes Ͻ RAPDs General congruence Peakall et al, 1995 Allozymes Ͻ RAPDs Large-scale concordance Puterka et al, 1993 Allozymes Ͻ RAPDs Allozymes Х RAPDs Allozymes Х RAPDs Ross et al, 1999 Similar Similar General congruence Sun et al, 1999 Allozymes Ͻ RAPDs Clustering pattern of isozymes has poorer discrimination power than for RAPDs Szmidt et al, 1996 b Allozymes Ͻ RAPDs Allozymes Х RAPDs Waycott, 1998 Allozymes Ͻ RAPDs Wu et al, 1999 Allozymes Ͻ RAPDs Allozymes Ͻ RAPDs Allozymes Х RAPDs a Depending on the species studied. Haploid tissue was analyzed in this study.…”
Section: Studymentioning
confidence: 99%
“…The larger number of loci resolved by RAPDs compared to allozymes, the selective neutrality of RAPDs and their ability to screen a larger part of the genome were cited as possible factors for the incongruences observed. Ayres and Ryan (1999) and Sun et al (1999) found that the dendrograms generated by combining the different markers reflected the geographical defined populations better than dendrograms based on only one type of marker. Many other studies demonstrated congruence between allozyme and RAPD based clusters (see Table 2).…”
Section: Studymentioning
confidence: 99%
“…Logically, there seems no reason why local endemics, if outcrossing and able to maintain genetic connectivity across large population sizes, should necessarily show reduced levels of genetic variation (BAWA and ASHTON, 1991). Indeed, once phylogenetic relationships are taken into account through comparisons between rare and widespread congeners (AYRES and RYAN, 1999;GITZENDANNER and SOLTIS, 2000), whilst average levels of diversity are lower in rare species, they show as wide a range of levels of diversity and of population differentiation as widely distributed species. In other words, generalisations are fraught with difficulty and each species should be considered a novel, unique entity (HAMRICK, 1983;GITZENDANNER and SOLTIS, 2000).…”
Section: Introductionmentioning
confidence: 99%